2018
DOI: 10.1080/10749357.2018.1465747
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 12-month task-specific balance training on the balance status of stroke survivors with and without cognitive impairments in Selected Hospitals in Nnewi, Anambra State, Nigeria

Abstract: Within the groups, a 12-month TSBT intervention significantly improved balance control, respectively, but with broader effects in the CIG than NCIG. Importantly, though between-group comparison at baseline revealed significantly impaired balance control in the CIG than NCIG, these differences were not significant at the 8th month and non-existent at the 12th month of TSBT intervention. These results underscore the robustness of TSBT to evenly address specific balance deficits of stroke survivors with and witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The sample sizes of the interventions were generally small, with 23 studies having sample sizes of less than 50 and 8 studies having sample sizes of 50–100, suggesting that studies with larger sample sizes should be conducted. There was also a lack of multi-center studies, and only one was a multi-center study ( 21 ).…”
Section: Resultsmentioning
confidence: 99%
“…The sample sizes of the interventions were generally small, with 23 studies having sample sizes of less than 50 and 8 studies having sample sizes of 50–100, suggesting that studies with larger sample sizes should be conducted. There was also a lack of multi-center studies, and only one was a multi-center study ( 21 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is interesting to note that the respondents did not accept that the stroke survivors presenting with visual impairment should be left untreated as a previous study by Okonkwo et al had noted that the cognitive status of sub-acute stokes survivors with compromised cognition could improve significantly as well as those of non-cognitive impaired stroke survivors when subjected to long-term proprioceptive neuromuscular facilitation (PNF) and task-specific balance training (TSBT) intervention (Okonkwo, Okoye, Ezeukwu, et al, 2017). Also, another of his study revealed that there was strong evidence to explain that adaptive neural plasticity induced by PNF and TSBT enhanced functional motor recovery and hence improved the QOL of cognitively impaired stroke survivors (Okonkwo, Okoye, Ibeneme, et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Of the 16 studies included in the scoping review, six studies reported baseline and follow-up BBS scores (Knox et al 2018;Okonkwo et al 2018;Vincent-Onabajo et al 2018;Puckree & Naidoo 2014;Olawale & Ogunmakin 2003). The median age of the study cohort in the chapter's primary prepost longitudinal study (48 years) was younger than the age range of these six studies (49.3-64.8 years).…”
Section: Discussionmentioning
confidence: 99%
“…However, the BBS has also demonstrated high floor and ceiling effects and is only moderately responsive to detect changes under 90 days since stroke onset (Mao et al 2002), suggesting that it may not be able to detect minor improvements in high-functioning individuals post-stroke (Salter et al 2013). This was evident in a few of the studies implementing the BBS in Africa (Okonkwo et al 2018;Puckree & Uthum 2014). The shortened version, called the miniBEST, was recommended as an alternative to address these limitations of the original BBS (Okonkwo et al 2018).…”
Section: Berg Balance Scalementioning
confidence: 99%
See 1 more Smart Citation